2011
DOI: 10.1111/j.1364-3703.2010.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Pantoea stewartii subsp. stewartii: lessons learned from a xylem‐dwelling pathogen of sweet corn

Abstract: http://www.apsnet.org/publications/apsnetfeatures/Pages/StewartsWilt.aspx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
132
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 50 publications
1
132
1
1
Order By: Relevance
“…In the fine-mapping populations, 194, 80, and 146 homozygous recombinants were screened for NLB in 2010, 2011, and 2012, respectively. Lines carrying mutations in the genes pan1 and pan2 were tested in Aurora, New York in 2011and in Ithaca, New York in 2011. Plants were inoculated with S. turcica isolate StNY001 (race 1), using previously described inoculation procedures (Chung et al 2010a).…”
Section: Disease Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fine-mapping populations, 194, 80, and 146 homozygous recombinants were screened for NLB in 2010, 2011, and 2012, respectively. Lines carrying mutations in the genes pan1 and pan2 were tested in Aurora, New York in 2011and in Ithaca, New York in 2011. Plants were inoculated with S. turcica isolate StNY001 (race 1), using previously described inoculation procedures (Chung et al 2010a).…”
Section: Disease Trialsmentioning
confidence: 99%
“…Both pathogens spread through the vascular tissue, causing wilted lesions by plugging xylem vessels (Jennings and Ullstrup 1957;Roper 2011). The importance of genes localized to maize bin 1.06 in resistance to both NLB and Stewart's wilt has been described in multiple mapping populations.…”
mentioning
confidence: 99%
“…Considering that 1 g of soil may harbor 10 3 -10 6 bacterial species (Torsvik et al, 1990;Curtis et al, 2002;Gans et al, 2005;Roesch et al, 2007), the vast majority would remain undetected. Community richness estimations in fact indicated that most of the diversity in the environment is due to rare members (Hughes et al, 2001;Reeder and Knight, 2009) and these may also have important ecological functions, for example, in cycling of elements, as a supplier of phytohormones or as phytopathogens (Karadeniz et al, 2006;Humbert et al, 2010;Pester et al, 2010;Roper, 2011;Krzmarzick et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…P. stewartii also possesses a hrp and wts gene cluster encoding a Hrp type III secretion system and effector proteins (8). Affected seedlings wither (wilt phase), and affected mature plants develop necrotic lesions (leaf blight phase), leading to losses in the crop yield (9). Other pathogenic Pantoea species include Pantoea ananatis, which causes soft rot of onions (10), and Pantoea citrea, which causes pink disease of pineapple (11).…”
mentioning
confidence: 99%